PROPOSED METHODOLOGY FOR IMPLEMENTING QUALITY METHODS AND TECHNIQUES IN MACEDONIAN COMPANIES - Mitreva, E.; Filipovski, O. (Journal of Engineering & Processing Management, 2012)
Providing quality in a business company is a matter related not only to the work done by individuals, but also with machines and the technology of the production processes as well. Therefore, it is necessary to provide statistical control in terms of estimating both the stability and the capability of production processes as well. However, control solely is not enough. A constant improvement of the processes by reducing the variants is necessary as well. Thus, it comes to the point that using SPC (Statistical Process Control) cannot be a mean of measuring the current performance. Instead, it provides a base for improvement of those processes. While designing the standard operative procedures, a suitable methodology for methods and techniques of SPC needs to be interposed, in order to perform a flawless production and methodology for optimization of costs. This paper provides a methodology proposal of SPC as a subsystem of the TQM (Total Quality Management) system that will assist managers in Macedonia in terms of designing a solid quality system. The proposed methodology provides a solid support of the top management, because the results gained from the outcomes of the partially implemented methods and techniques at some companies in Macedonia indicate that implementing SPC methodology and methodology of costs optimization can help achieving both the defined quality and better productivity by smallest costs. These methods have given same effects in number of diverse companies which refers to the universality of the proposed methodology.